2009
DOI: 10.1002/jsfa.3829
|View full text |Cite
|
Sign up to set email alerts
|

Development and in‐house validation of the event‐specific qualitative and quantitative PCR detection methods for genetically modified cotton MON15985

Abstract: This study shows that the developed qualitative and quantitative PCR methods are applicable for the identification and quantification of GM cotton MON15985 and its derivates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 10 publications
1
10
0
1
Order By: Relevance
“…These results indicated that the event‐specific quantitative PCR assay for Huafan No. 1 was reliable for quantification of GM tomato samples, in comparison with another paper in our laboratory for GM cotton MON15985 …”
Section: Resultsmentioning
confidence: 79%
“…These results indicated that the event‐specific quantitative PCR assay for Huafan No. 1 was reliable for quantification of GM tomato samples, in comparison with another paper in our laboratory for GM cotton MON15985 …”
Section: Resultsmentioning
confidence: 79%
“…[14][15][16] An increasing number of countries and regions have passed strict laws and regulations requiring the labeling of GM food products and detailed safety studies of any transgenic crops before they are approved for commercial production. [17][18][19] For food safety evaluation of GM crops, a major principle and guidance named substantial equivalence was proposed by the Food and Agriculture Organization (FAO) and World Health Organization (WHO) in the early 1990s. [20][21][22] According to the substantial equivalence guideline, various methodologies, including cDNA microarray, miRNA fingerprinting, proteomics, metabolomics and toxicological profiling, need to be applied to investigate the differences between transgenic organisms and their counterpart parental or other wild type lines.…”
Section: Resultsmentioning
confidence: 99%
“…Detection and quantification limits refer to the lowest quantity of the target that can be reliably detected and quantified with a probability of ≥ 95%. The absolute limit is the lowest number of initial template copies that can be detected and quantified . To determine the LOD and LOQ of the established event‐specific RT‐PCR assay, series of DNA dilutions containing an estimated average of 100 000, 10 000, 1000, 100 and 10 copies of the EE‐1 brinjal haploid genome per reaction were tested in triplicate in three parallel reactions (Table ).…”
Section: Resultsmentioning
confidence: 99%